Estudo da hidrólise e fermentação dos resíduos de milho (Zea mays) para produção de etanol de segunda geração - Carvalho, Lívia Luísa Melo de (2016)
In the current context of the demand for bioproducts from renewable sources and concern for environmental conditions makes biofuels, which are produced from biomass, an alternative to the global dependence on oil products. Thus, there is a growing appreciation of residues from the agricultural industry as a source of lignocellulosic raw material for the production of ethanol 2G (second generation ethanol). In this sense, the objective of this study was to evaluate the steps of hydrolysis and fermentation broth hydrolytic straw and corn cobs for second generation ethanol production, testing different process conditions. Therefore, pretreated corn stover were used with H2SO4 0.5% at 121 ° C for 15 minutes in enzymatic hydrolysis tests rotary incubator shaker table type at 50 ° C and 150rpm, using 20FPU / mL enzyme Cellic Ctec 2®, ranging biomass load, hydrolysis time and type of biomass according to the experimental design, which enabled study of the best hydrolysis operating conditions, by observing the effects and combinations of parameters, where the best ART index (g / L) was at the straw with 5 g biomass for 48 hours to give 30,68g / L in the investigated range. The fermentation was conducted at 30 ° C in a shaker, 200 rpm for 24h fermentation with 90.97% efficiency, yielding 3.9g / L of ethanol.